2005
DOI: 10.1093/humrep/dei126
|View full text |Cite
|
Sign up to set email alerts
|

Gene deletions in an infertile man with sperm fibrous sheath dysplasia

Abstract: In this infertile patient, our results suggest a possible relationship between dysplasia of the fibrous sheath, partial deletions in the Akap3 and Akap4 genes and absence of AKAP4 protein in the fibrous sheath. These findings, however, were not detected in another four patients with dysplasia of the fibrous sheath. Our results require future confirmatory molecular analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 20 publications
1
90
0
3
Order By: Relevance
“…2,3,15,16 However, the biallelic DNAH1 mutations identified in previous studies only accounted for 28%-44% of MMAF. 3,17,18 These observations suggested the existence of unknown genes associated with MMAF.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…2,3,15,16 However, the biallelic DNAH1 mutations identified in previous studies only accounted for 28%-44% of MMAF. 3,17,18 These observations suggested the existence of unknown genes associated with MMAF.…”
Section: Discussionmentioning
confidence: 88%
“…2,[10][11][12][13][14] So far, mutations in only three genes, AKAP4 (MIM: 300185), CCDC39 (MIM: 613798), and DNAH1 (MIM: 603332), have been formally identified to cause MMAF in humans. 2,3,15,16 Among them, biallelic DNAH1 mutations in MMAF have been recurrently identified across studies and account for 28%-44% of MMAF cases. 3,17,18 However, the genetic causes or molecular mechanisms in the other half of MMAF cases are still unclear, indicating the genetic heterogeneity of MMAF.…”
Section: Introductionmentioning
confidence: 99%
“…However, consistent human data were reported from only one study. Baccetti et al [90] used PCR and observed intragenic deletions of AKAP4 and AKAP3, which code for major structural components of the fibrous sheath, in one DFS patient. No abnormality was detected in other samples.…”
Section: Dysplasia Of the Fibrous Sheath Of The Tailmentioning
confidence: 99%
“…It was demonstrated that the absence of these proteins is associated to sperm immotility [10,8,11]. Baccetti et al, [11] have reported in one DFS patient a deletion of the AKAP4/AKAP3 binding regions and have suggested that in some cases the DFS sperm defect could be associated with alterations of AKAP3 and AKAP4 gene sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Several proteins have been identified on isolated human sperm fibrous sheath [6,7], and only two proteins AKAP3 and AKAP4 (members of the A-kinase anchor protein family) involved in organizing the basic structure of the fibrous sheath [8] were described as the most abundant structural protein of the fibrous sheath [9]. It was demonstrated that the absence of these proteins is associated to sperm immotility [10,8,11]. Baccetti et al, [11] have reported in one DFS patient a deletion of the AKAP4/AKAP3 binding regions and have suggested that in some cases the DFS sperm defect could be associated with alterations of AKAP3 and AKAP4 gene sequences.…”
Section: Introductionmentioning
confidence: 99%